Correlation Between Digital Literacy Ability and Learning Achievement in Physics Learning During Covid-19 Pandemic - Mardiana Lea; Haris Rosdianto; Emi Sulistri; Chat Teeka (STKIP Singkawang, 2023)
This study aims to: (1) describe students' digital literacy skills in physics learning during the Covid-19 pandemic and (2) describe the correlation between digital literacy skills and learning achievement in physics learning during the Covid-19 pandemic. This research is using correlation research. The subjects in this study were students of class X at SMKN 4 Singkawang City. The data collection instruments in this study were digital literacy questionnaires and documentation. The data analysis techniques used in this study were quantitative descriptive and Product Moment correlation equations. The results showed that: (1) the students' digital literacy skills at SMKN 4 Singkawang were in the high category of 90 students with an average percentage of 69% and an average score is 79 and (2) there was a correlation between digital literacy skills and student achievement in physics learning during the Covid-19 pandemic with a correlation coefficient of 0.664 in the strong category.